THE EFFECTIVE USE OF NONVERBAL TOOLS IN CREATING THE IMAGE OF HEROS ON THE STAGE. - Gozal, Khalikulova (International Journal of Psychosocial Rehabilitation, 2020)
The paper focuses on the theoretical foundations, functions, and criteria of acting, and the studies of the stages of formation and development of the Uzbek theater that has been evolving for decades. As well as that, it critically analyzes the methods used in the education of actors and directors that enables conclusions about the status quo to be derived and problems of theatrical performances to be identified, at the same time introducing well- developed techniques so as to implement them further. Additionally, successful Uzbek Theater performances and actors are given special attention and mentioned with examples. Lastly, the way actors use verbal and nonverbal techniques are scientifically based, and suggestions and recommendations are offered.